Analysis of the Effect of Supply Chain Management on Competitive Advantage and Company Performance - Asyriana Br. P, Sofia (Universitas Prasetiya Mulya, 2024)
This study wanted to know whether there was a basic effect of Creation network The board to high ground and company's show. Stock organization The leaders factors assessed by 3 pointers, to be explicit Fundamental Supplier Association, Client Relationship, and Information Sharing. Advantage factors assessed by 5 pointers, to be explicit expense, quality, transport consistency, thing advancement, and time to grandstand. While the association's show factors assessed by 2 pointers, explicitly money related execution and utilitarian execution. The data were assembled by spreading surveys. The unit of assessment of the investigation was associations in Surabaya. Respondents were 90 managers. The assessment procedure used in testing the hypothesis was Basic Condition Showing (SEM) by using Partial Least Square (PLS). This study had the choice to show the presence of a basic relationship of Creation network The leaders to high ground, Stock organization The board to association execution, and as well as Advantage to Association's Show.